2019
DOI: 10.22175/mmb2019.07.0030
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Enhancement Strategies of Beef Flanks on Composition and Consumer Palatability Characteristics

Abstract: Beef rectus abdominis muscles (n = 100; 20/treatment) were assigned randomly to 1 of 5 treatments: untreated control (Control, No Treatment; CNT), vacuum tumbled control without marinade (Tumbled Control, No Treatment; TCNT), vacuum tumbled with marinade (TUMB), injected with marinade (INJ), and injected with marinade plus vacuum tumbled (IPT) to determine how enhancement techniques influence consumer palatability. After processing, flank samples were cooked (72°C), cut into 1.3-cm strips, and served as fajita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
6
16
0
Order By: Relevance
“…It could be postulated that tumbling would result in larger gaps between cooked muscle fibers, resulting in more cooking loss (Pearce et al, 2011). Morrow et al (2019) found cooking loss of beef rectus abdominus muscles tumbled without brine to be higher relative to the nontumbled control, in agreement with the findings in the present study. However, despite increased cooking loss, moisture content of both the raw and cooked products were equivalent, and consumer juiciness scores between tumbled without brine and control muscles were comparable (Morrow et al, 2019).…”
Section: Water-holding Abilitysupporting
confidence: 91%
See 1 more Smart Citation
“…It could be postulated that tumbling would result in larger gaps between cooked muscle fibers, resulting in more cooking loss (Pearce et al, 2011). Morrow et al (2019) found cooking loss of beef rectus abdominus muscles tumbled without brine to be higher relative to the nontumbled control, in agreement with the findings in the present study. However, despite increased cooking loss, moisture content of both the raw and cooked products were equivalent, and consumer juiciness scores between tumbled without brine and control muscles were comparable (Morrow et al, 2019).…”
Section: Water-holding Abilitysupporting
confidence: 91%
“…However, it is poorly understood how quality of fresh beef would be affected through the application of tumbling without the use of a brine solution. Recently, Morrow et al (2019) observed no positive effect of tumbling without brine on tenderization of beef rectus abdominus muscles. However, beef tenderization is known to be muscle-specific (Juárez et al, 2010;Kim et al, 2018b;Nair et al, 2019), and the flank muscle is often described as tougher than the loin owing to larger muscle fibers and higher amount of connective tissue (Jeremiah et al, 2003;Couvreur et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Enhancement can increase muscle pH and decrease free water, increasing moisture retention [5,24]. Morrow et al [10] found that enhanced flank steaks had a greater cooked moisture percentage than non-enhanced samples, and consumers scored those enhanced samples as juicier. Flavor liking and overall liking increased in the current study due to enhancement, again aligning with previous results [5,6,24].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, saltiness did not appear to be overwhelming or detrimental in the current results, as flavor liking improved with enhancement. Likewise, Morrow et al [10] had consumers score flank steaks for saltiness using "Just about right" scales, where 50 was "Just about right". Their brine solution had a similar salt concentration as the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation